Application of Ethics in Police Duties Between Obligations and Responsibilities - Yehezkiel Yehezkiel; Basrawi Basrawi; Reka Alfionita Burhan; Hesti Anas Tasya; Ahmad Fauzi; Andi Wandiyensa (Sangia Nibandera Law Research, 2025)
The application of ethics in law enforcement is an important area of study, especially as police officers navigate the complexities of their role in society. This paper examines the relationship between legal obligations and moral responsibilities in police work, with a focus on how ethical considerations shape police practice. Using a mixed-methods approach, this research integrates qualitative interviews with law enforcement officials and quantitative surveys to gather insights into ethical challenges in daily operations. Findings suggest that officers often face dilemmas when legal mandates conflict with ethical imperatives, leading to tensions between law enforcement and justice. Key areas of concern include use of force, racial profiling, and transparency of police behavior. This study highlights the importance of ethics training programs that equip officers to make decisions under pressure. The report also emphasizes the role of leadership in fostering a culture of integrity in police departments. This research discusses the implications of ethical policies for public relations, showing that compliance with ethical standards can increase public trust. By comparing successful case studies with examples of ethical violations, this paper illustrates the consequences of neglecting ethical responsibilities. Ultimately, this research advocates a comprehensive framework that integrates ethical considerations into all aspects of police work, ensuring a balance between legal duties and commitment to society.